The Christological controversy - Norris, Richard A., Jr. (Richard Alfred), 1930-2005. (Philadelphia : Fortress Press, 1980)
This book is a collection of texts designed to illustrate the development of Christian thought about the person of Christ in the patristic era. The earliest text translated comes from the latter half of the second century, when the ideas and problems which were to dominate Christological thought in this period were first crystallized. The latest is the well-known "Definition of the Faith" of the Council of Chalcedon, which generally has been accepted as defining the limits of Christological orthodoxy
Introduction : Early Christology -- Initial problems : Justin Martyr, Melito of Sardis, Irenaeus of Lyon, Tertullian of Carthage, Origen of Alexandria -- Further problems : The Arians and Athanasius ; Appollinari of Laodicea ; Theodore of Mopsuestia ; Cyril, Nestorius, and Eutyches ; Leo and Chalcedon -- A homily on the Passover / Melito of Sardis -- Against heresies / Irenaeus of Lyon -- Against Praxeas
Includes bibliographical references (pages 161-162)
Keywords: Jesus Christ -- History of doctrines -- Early church, ca. 30-600